PENGARUH KUALITAS KEHIDUPAN KERJA, KOMITMEN ORGANISASIONAL, DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI (STUDI PADA DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN DEMAK) - Hadi Warsito, 10.05.51.0064; Suko Priyono, Bambang (Students Journal of Economic and Management, 2014)
This research is a study that tested the effect of the quality of work life, organizational commitment, and motivation off employee satisfaction. The purpose of this study is: 1) examine the effect of the quality of work life on job satisfaction. 2) examine the effect of organizational commitment on job satisfaction. 3) examine the effect of motivation on job satisfaction. This study was conducted on social services employee manpower and transmigration kab.demak. a sample of respondents in this study were 102 respondents. The sampling methodwas census sampling method, in which all population is used as a sample. The data used primary data, data analisis using quantitative and qualitative test which includes validity, reliability test, normality test, multiple regresion analysis, t test, F test, and the coefficient of determination. The result showed that, the first hypothesis there is a positive influence on yhe quality of work life employee satisfaction social service manpower and ransmigration kab. Demak. The second hyphotesis there is a positive effect of organozational commitment on job employees of social service manpower and transmogration kab.demak. the third hypothesis there is a positive influence on job satisfaction employee motivation social service manpower and transmogration kab.demak.Key words: quality of work life, organizational commitment, motivation, and job satisfaction.